The implementation of a push-pull programme for the control of Eldana saccharina (Lepidoptera: Pyralidae) in sugarcane in the coastal regions of Kwazulu-Natal, South Africa - Mulcahy, Megan Marie (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2018)
Eldana saccharina, an indigenous lepidopteran stemborer, is considered the most damaging pest of sugarcane in South Africa. Researchers have advocated the use of an area-wide integrated pest management (AW-IPM) programme as a means of improving the control of this pest. A push-pull strategy was developed as a component of this AW-IPM approach. The push-pull strategy in sugarcane is a habitat management method of pest control that uses plants that are both repellent (Melinis Minutiflora) and attractive (Cyperus dives, Cyperus papyrus and Bt-maize) to E. saccharina. Previous research into push-pull has shown that this strategy is an effective tool for the control of E. saccharina. Push-pull has been implemented successfully in the Midlands North sugarcane growing region of KwaZulu-Natal (KZN), South Africa. Despite the proven efficacy of push-pull, very little push-pull research has been conducted in the coastal sugarcane growing regions of KZN, and adoption of this technology has been poor in these regions. Therefore, the aim of this research was to facilitate the implementation of push-pull for the management of E. saccharina in sugarcane in the coastal regions of KZN. This was done by focussing on on-farm field trials and farmer participatory research. On-farm push-pull field trials were conducted on five model farms in the North and South Coast sugarcane growing regions of KZN. High levels of E. saccharina were recorded during this study. The push-pull treatment sites showed a significant reduction of E. saccharina damage on four of the five farms used in the study. Mean percentage of stalks damaged decreased by up to 50 % in the presence of the repellent grass species, M. minutiflora. The number of E. saccharina found per 100 stalks also decreased significantly at these farms. The farm which did not show a significant reduction in E. saccharina populations or damage had low numbers of this pest in the sugarcane throughout the experiment. This demonstrates that push-pull is more effective in areas that have high levels of E. saccharina. Stem borer surveys in wetlands on sugarcane farms revealed that high numbers of E. saccharina were found within the pull plants, C. papyrus and C. dives, in comparison to the push-pull sites. This verifies that the pull plants do work efficiently to attract E. saccharina away from sugarcane. Additionally, eight parasitoids emerged from E. saccharina larvae collected in wetland sedges. The beneficial roles that push-pull plants play in attracting and maintaining natural enemies in the agroecosystem are discussed, and these findings further demonstrate the important ecosystem, and pest management services that wetlands provide on sugarcane farms. The success of the push-pull trials in this study show that this technology can be an effective tool for controlling E. saccharina in the coastal sugarcane growing regions. The timing of the planting of push-pull plants was shown to play a role in the efficacy of this technology. The study also confirmed that push-pull should be used as a component of AW-IPM in conjunction with good crop management practices. Surveys were undertaken to determine large-scale sugarcane growers' (LSGs) knowledge and perceptions of E. saccharina and other pests. Research regarding the farmers' perceptions of push- pull was also conducted to better understand the drivers and barriers to adoption of push-pull, and other new technologies. The surveys found that large-scale farmers in the coastal regions suffer from high infestations of E. saccharina. As such there is scope for the introduction of new pest management practices such as push-pull in this area. Farmers also demonstrated a good basic knowledge of E. saccharina and IPM. However, LSGs had a poor understanding of push-pull and how it works, as well as the plants that make up the push-pull system that is being implemented against E. saccharina in South Africa. A dearth in practical knowledge regarding the implementation of push-pull was seen as a major barrier to the adoption of this strategy, as was financial instability, farmer attitudes and poor institutional support. Farmers recommended collaboration amongst stakeholders, improved education, proof of the efficacy of push-pull and incentives as tools to improve the implementation of this strategy in the coastal sugarcane growing regions of KZN. Farmers preferred direct contact with extension personnel and experiential learning opportunities when acquiring information about push- pull and other new pest management practices. If opportunities for push-pull education are increased through direct contact with extension personnel, and through on-farm demonstrations, and if inputs are provided in the form of push-pull plants, it is likely that push-pull will succeed amongst coastal LSGs, especially since farmers had an overall positive attitude towards the technology. Surveys amongst small-scale sugarcane growers (SSGs) showed that sugarcane is important in the lives of these farmers. The SSGs perceive pests to be a major constraint to their farming systems, and they identified E. saccharina as a major pest of sugarcane. The farmers also demonstrated good knowledge of sugarcane pests and vegetable pests. However, SSGs lacked knowledge regarding pest management practices and beneficial insects. Extension and advisory services should to continue concentrating on pest management practices to educate SSGs on the variety and application of pest control strategies. SSGs were found to employ complex, diverse and integrated agricultural systems that are well-suited to the implementation of IPM technologies such as push-pull. Since insect pests act were found to be a major constraint to SSG sugarcane production, push-pull was deemed a feasible pest management strategy for coastal farmers and its implementation by SSGs should be further explored. SSGs in this study were also concerned about vegetable pests, therefore if push-pull can be adapted to help protect additional crops, adoption of this technology by small-scale growers will improve.
Keywords: Pyralidae -- South Africa -- KwaZulu-Natal; Pests -- Integrated control; Sugarcane -- Diseases and pests -- South Africa -- KwaZulu-Natal; Stem borers -- Effect of habitat modification on -- South Africa -- KwaZulu-Natal; Insect-plant relationships -- South Africa -- KwaZulu-Natal